Major adverse cardiac events and functional capacity in patients at intermediate risk undergoing transcatheter versus surgical aortic valve replacement for aortic stenosis with bicuspid valves. Issue 3 (11th January 2021) - Tsai, Hui‐Yu; Lin, Yu‐Shan; Wu, I‐Chen; Kuo, Li‐Ying; Chen, Bo‐Yan; Shen, Shiang‐Lin; Hsu, Wei‐Ning; Huang, Hsin‐Yi
Abstract: Background: Transcatheter aortic valve replacement (TAVR) is not always the optimal option for aortic valve stenosis (AS) patients with bicuspid aortic valves (BcAVs) and many studies exclude this group of patients. The aim of our study was to compare the rate of a major adverse cardiovascular event (MACE) and functional capacity in AS patients with BcAV after surgical aortic valve replacement (SAVR) and TAVR. Methods: This study included 130 patients who underwent SAVR or TAVR from July 2013 to August 2018 at the Cheng Hsin General Hospital. The main outcome was MACE. Events recorded included noncardiovascular (CV) mortality, CV mortality, recurrent nonfatal stroke, recurrent nonfatal myocardial infarction (MI), and important events. The secondary outcome was functional recovery, which was defined according to the metabolic equivalent (MET) 6 months after the aortic procedure. Results: The mean age of patients was 56.8 ± 26.9 years and the mean Society of Thoracic Surgeons score was 3.29 ± 4.69. Logistic regression analyses indicated that SAVR was a significant predictor of functional recovery. Patients who underwent SAVR had a higher rate of functional recovery (>3 METs; 87.8%, p  = .000) and had a significantly higher odds ratio (3.56; 95% confidence interval, 1.19–10.63, p  = .023). The Kaplan–Meier survival analysis showed that the MACE rate was not associated with the aortic procedure. Conclusions: Our analysis showed that SAVR is a significant predictor of better functional recovery and TAVR is associated with a lower level of functional capacity. In summary, TAVR is an acceptable option for AS patients with BcAV, and for a better prognosis, an early intervention aimed at improving functional capacity is highly recommended for this group of patients.